Relationship between metabolic parameters and stroking technique characteristics in front crawl - Wakayoshi, K.; D'Acquiato, J.; Cappaert, J. M.; Troup, J. P. (Biomechanics and Medicine in Swimming VII, 1996)
The purpose of this study was to determine the relationship between physiological parameters and stroking technique characteristics in front crawl. Subjects performed a swimming economy test for determination of steady-state oxygen uptake (V02) and an incremental swim test to volitional exhaustion for determination of peak aerobic power . (V02peak). Two additional swim efforts were performed at velocities corresponding to 80 and 1000/oV02peak (V80%V02peak and V100%V02peak). Stroke length (SL), stroke rate (SR) and velocity at the onset of blood lactate accumulation (VOBLA) were determined to assess stroking technique and endurance ability. For each sub-maximal effort, SL and SR remained unchanged throughout the six minute swim, and V02 was found to reach steady-state levels. During the 80 and 1 000/o V02peak swims, SL and SR showed significant decreases and increases, respectively. V02 increased significantly throughout the 80 and 100% V02peak swims. Lactate threshold (LT) corresponded to an average velocity of 1.3 m/sand a mean VOBLA of 1.423±0.017 m/s. These results suggest that stroking technique remained unchanged during swimming activities corresponding to aerobic intensities, but changes in swimming mechanics occurred in order to maintain pace at anaerobic workloads.